Latin and Coptic: Languages, Literatures, Cultures in Contact - Scappaticcio, Maria Chiara; Pezzella, Alessia (Testi. Antichità, Medioevo e Umanesimo, 2022)
This volume is the first work devoted to the contacts between Latin and Coptic in late antique and Byzantine Egypt. It follows in the footsteps of a renewed interest in this multilingual and multicultural area, but it approaches an untapped theme aiming to show that it can profitably be explored. The papers examine different type of evidence on the basis of a multi-perspective approach. Some of them deal with wide-ranging issues, such as the presence of Latin in monastic or scholastic contexts alongside local varieties, some others deal with specific subjects, such as the use of Latin in a certain milieux or in specific documents. All papers show that the contact between languages, scripts and cultures took many forms depending on various factors.